2021
DOI: 10.1007/s00424-021-02577-4
|View full text |Cite
|
Sign up to set email alerts
|

The erythropoietin receptor expressed in skeletal muscle is essential for mitochondrial biogenesis and physiological exercise

Abstract: Erythropoietin (EPO) is a haematopoietic hormone that regulates erythropoiesis, but the EPO-receptor (EpoR) is also expressed in non-haematopoietic tissues. Stimulation of the EpoR in cardiac and skeletal muscle provides protection from various forms of pathological stress, but its relevance for normal muscle physiology remains unclear. We aimed to determine the contribution of the tissue-specific EpoR to exercise-induced remodelling of cardiac and skeletal muscle. Baseline phenotyping was performed on left ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…EPOR is present not only in hematopoietic cells but also in non-hematopoietic cells such as neurons ( 10 ), endothelial cells ( 11 ), and skeletal muscle cells ( 33 ) and in various tumors such as breast cancer ( 34 ) and head and neck cancer ( 35 ). Regarding EPOR expression in cancers, on the one hand, it is believed that EPOR expression is upregulated, such as in prostate cancer ( 21 ) and glioma ( 22 ); on the other hand, no significant EPOR expression was detected in tumor cell lines and solid tumor specimens, and Swift et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EPOR is present not only in hematopoietic cells but also in non-hematopoietic cells such as neurons ( 10 ), endothelial cells ( 11 ), and skeletal muscle cells ( 33 ) and in various tumors such as breast cancer ( 34 ) and head and neck cancer ( 35 ). Regarding EPOR expression in cancers, on the one hand, it is believed that EPOR expression is upregulated, such as in prostate cancer ( 21 ) and glioma ( 22 ); on the other hand, no significant EPOR expression was detected in tumor cell lines and solid tumor specimens, and Swift et al.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in the study, we aimed to explore the feasibility of EPOR as a prognostic marker and its role in tumor immunity, tumor occurrence, and progression through bioinformatics techniques. EPOR is present not only in hematopoietic cells but also in non-hematopoietic cells such as neurons (10), endothelial cells (11), and skeletal muscle cells (33) and in various tumors such as breast cancer (34) and head and neck cancer (35). Regarding EPOR expression in cancers, on the one hand, it is believed that EPOR expression is upregulated, such as in prostate cancer (21) and glioma (22); on the other hand, no significant EPOR expression was detected in tumor cell lines and solid tumor specimens, and Swift et al (36) suggested that low levels of EPOR expression are common in tumor cell lines, Elliott et al (37) questioned the assumption that most tumors express high levels of functional EPOR proteins, and Patterson et al (38) did not detect the utilization of the functional EPOR pathway in primary tumor cells isolated from tumor tissues such as human breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies with mouse models have shown a 4–7 fold increase in EPO mRNA expression in skeletal muscle following exercise, and the increase was higher in glycolytic muscles and for trained mice [ 26 ]. The most recent data indicate that the endogenous EPO, through the EPO receptor in myocytes, controls mitochondrial biogenesis in skeletal muscle [ 27 ]. Nijholt et al showed that a lack of EPO receptors in non-haematopoietic tissues lead to low mitochondrial content in skeletal muscles, as well as reduced myocyte growth and exercise capacity in response to voluntary exercise in mice [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent data indicate that the endogenous EPO, through the EPO receptor in myocytes, controls mitochondrial biogenesis in skeletal muscle [ 27 ]. Nijholt et al showed that a lack of EPO receptors in non-haematopoietic tissues lead to low mitochondrial content in skeletal muscles, as well as reduced myocyte growth and exercise capacity in response to voluntary exercise in mice [ 27 ]. Thus, it may be suggested that the source of erythropoietin released into circulation as a result of physical exertion may not only be from the kidneys but—at least in the early stages of exercise—from the working skeletal muscles as well [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…In skeletal muscle, improvements in mitochondrial quality control could enhance the adaptive response to stress and block or reverse the unfavourable muscle fibre switching. Recently, our department uncovered an important role of the erythropoietin receptor in skeletal muscle, a novel target which is critical for mitochondrial biogenesis in skeletal muscle and the response to physiological exercise 155 . Potentially, stimulating skeletal muscle erythropoietin signalling could benefit for patients with mitochondrial myopathies, skeletal muscle fatigue, or atrophy.…”
Section: Possibilities To Improve Exercise Intolerance In Heart Failurementioning
confidence: 99%